Peran Kepolisian Dalam Meminimalisir Penyalahgunaan Narkoba di Lingkungan Pelajar - Halima Hamzah (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2022)
This study aims to analyze the role of the police in tackling narcotics abuse by students in Biak Numfor Regency and the inhibiting factors in tackling narcotics abuse by students. The approach in this study was empirical juridical approach. The results showed that the Biak’s Regional Police as a law enforcement agency in preventing and eradicating narcotics crimes among students can be seen from the performance of its staff who actively collaborate with other agencies and the community in breaking the chain of narcotics circulation. Biak’s Regional Police took steps to prevent and eradicate this drug crime, namely non-penal and penal efforts. The police are maximizing non-penal efforts, namely pre-emptive and preventive actions, because these efforts are more effective. Inhibiting factors are internal and external barriers. Internal obstacles emerge when conducting open raids, frequent leakage of operational targets for raids and the lack of operational funds. External obstacles are caused by the absence of support/cooperation from the local community